2012
DOI: 10.1007/s00449-012-0696-2
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of semiconductor volatile organic compounds by four novel bacterial strains: a kinetic analysis

Abstract: This study isolated pure microorganisms for further bioreactor applications. Four novel strains of Pseudomonas citronellolis YAIP521, Paracoccus versutus HSAC51, Burkholderia sp. HUEL671, and Pseudomonas aeruginosa JUPG561 were isolated and tested for biodegradation of isopropyl alcohol (IPA), acetone, ethyl lactate (EL), and propylene glycol mono methyl ether acetate (PGMEA), respectively. The maximum biodegradation rates for IPA, acetone, EL, and PGMEA were 5.27, 3.87, 26.86, and 48.93 mg L(-1) h(-1), respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The filter media surface consisted of biofilms of a pure culture Pseudomonas citronellolis YAIP521 purified from a wastewater treatment system at Hsinchu Science‐based Industrial Park (HSIP) in Taiwan and were inoculated before use. GenBank BLAST analysis of 16S rRNA gene (http://www.ncbi.nlm.nih.gov) of YAIP521, based on the sequence of a ∼1400‐bp fragment revealed that the accession number, percentage of similarity and E values for the matching score (indicated in parentheses) is Pseudomonas citronellolis strain TERIDB26 (AF530073.1, 99%, 0.0) , …”
Section: Methodsmentioning
confidence: 99%
“…The filter media surface consisted of biofilms of a pure culture Pseudomonas citronellolis YAIP521 purified from a wastewater treatment system at Hsinchu Science‐based Industrial Park (HSIP) in Taiwan and were inoculated before use. GenBank BLAST analysis of 16S rRNA gene (http://www.ncbi.nlm.nih.gov) of YAIP521, based on the sequence of a ∼1400‐bp fragment revealed that the accession number, percentage of similarity and E values for the matching score (indicated in parentheses) is Pseudomonas citronellolis strain TERIDB26 (AF530073.1, 99%, 0.0) , …”
Section: Methodsmentioning
confidence: 99%